Analisis Pelaksanaan Pelayanan Antenatal pada Masa Pandemi Covid-19 - Mugiati, Mugiati; Rahmayati, El (Jurnal Kesehatan, 2021)
Pregnant and lactating women are susceptible to viral infections including Covid-19. One of the reasons is low immunity due to hormonal changes during pregnancy and breastfeeding. the Ministry of Health has made guidelines for pregnant women, childbirth, and newborns during the Covid-19 pandemic. The purpose of this study was to describe the implementation of antenatal care services during the Covid-19 Pandemic. This study analysis of this research sample of pregnant women and midwives in the Puskesmas Way Kandis work area which were taken purposively. the study began by conducting interviews with 4 midwives to get an overview of the implementation of antenatal services, then online data collection was carried out on pregnant women, the analysis was carried out with a systems approach theory. Analysis of the implementation of antenatal services during the Covid-19 pandemic was seen from the input factors, namely characteristics, with the results that 86,6% of respondents were of healthy reproductive age and 72,2% were multiparous.Â Process: midwives conduct home visits to guide pregnant women in studying the MCH handbook. Output factor: the results of the analysis of the knowledge of the mother, 43% have sufficient knowledge, and 35% have less knowledge. The obstacle for midwives is the non-compliance of the community, especially pregnant women and cadres, in implementing protocols when visiting health services. It is recommended that Puskesmas be more intensive in providing education to pregnant women and their families as well as fostering health cadres to comply with the implementation of health protocols.